2022
DOI: 10.5658/wood.2022.50.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Furfurylation Effects on Discoloration and Physical-Mechanical Properties of Wood from Tropical Plantation Forests

Abstract: Wood from tropical plantation forests has lower physical and mechanical properties than mature wood. Furfuryl alcohol (FA) impregnation into the wood could help to enhance hydrophobic properties, dimensional stability, and structural strength. Furfurylation was applied to specimens of the following four fast-growing tropical wood species: jabon (Anthocephalus cadamba), sengon (Falcataria moluccana), mangium (Acacia mangium), and pine (Pinus merkusii). The discoloration and physical and mechanical properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…The density, WPG, BE, WU, and ASE of untreated and treated samples are presented in The increase in the density of sengon wood in this study was followed by increased WPG value in agreement with the results of Hadi et al (2022), who reported that the furfurylated sample had a higher density than the untreated sample and the increase in WPG value followed the increase in density. The higher the density of the treated wood, the greater the content that filled the wood cell walls and the thicker the wood cell walls (Bowyer et al, 2007).…”
Section: Dimensional Stability Of Sengon Woodsupporting
confidence: 90%
“…The density, WPG, BE, WU, and ASE of untreated and treated samples are presented in The increase in the density of sengon wood in this study was followed by increased WPG value in agreement with the results of Hadi et al (2022), who reported that the furfurylated sample had a higher density than the untreated sample and the increase in WPG value followed the increase in density. The higher the density of the treated wood, the greater the content that filled the wood cell walls and the thicker the wood cell walls (Bowyer et al, 2007).…”
Section: Dimensional Stability Of Sengon Woodsupporting
confidence: 90%
“…In summary, there was a significant difference in color (ΔE) between the untreated wood samples (control) and wood samples impregnated with catechin solutions. This finding is relevant to the study by Hadi et al (2020Hadi et al ( , 2022, who reported that any chemical treatment of wood could potentially change its natural color. However, no color differences were observed among the wood samples treated with catechin solutions at concentrations of 9%, 12%, and 15%.…”
Section: Discoloration After Exposure To the Stain Fungisupporting
confidence: 52%
“…Before coloring, the bamboo strips were first measured for L, a*, and b* values using a Minolta CR-400 Chroma Meter. After the coloring process, the bamboo strips were again measured for L, a*, and b* values using the same tool and the color change test results will be compared with the standards in table 1 [9]. This research used 5 samples for each treatment, and in one Color change is calculated using the following formula: The scale of color change in dyed bamboo is listed in the following table [9]: The form of this research design is a completely randomized design with a factorial experiment that has two factors, namely the type of coloring and the presence of preservatives, with each factor having two levels.…”
Section: Preservatives Addition In Dyes Solutionmentioning
confidence: 99%